2021
DOI: 10.24840/esc.vi58.115
|View full text |Cite
|
Sign up to set email alerts
|

Sobre a Investigação nos Programas de Formação Inicial de Professores

Abstract: A consciência da importância da formação inicial tem crescido nos últimos anos e a formação em investigação surge como uma dimensão a investir para a qualidade da formação e do ensino. É também sabido que os contextos nacionais têm impacto na maneira como a formação inicial de professores é estruturada e, portanto, na maneira como a investigação é valorizada. Pretende‑se comeste trabalho descrever e discutir a relação que se estabelece entre a investigação e o ensino na formação inicial de professores em dois … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…They generally look for practical and concrete examples that may help them as future teachers. In a comparative study between initial teacher education in Portugal and England, Sousa et al (2021) found differences in how the teacher students related the importance of research in relation to their professional competence as teachers. The Portuguese students tended to emphasise the significance of research to inform practice more than their English peers.…”
Section: Research and Practice In Teacher Education And Teachers' Workmentioning
confidence: 99%
“…They generally look for practical and concrete examples that may help them as future teachers. In a comparative study between initial teacher education in Portugal and England, Sousa et al (2021) found differences in how the teacher students related the importance of research in relation to their professional competence as teachers. The Portuguese students tended to emphasise the significance of research to inform practice more than their English peers.…”
Section: Research and Practice In Teacher Education And Teachers' Workmentioning
confidence: 99%